Coupled Fixed Point Results in Complete Partial Metric Spaces. (30th October 2012) - Alaeidizaji, H.; Parvaneh, V.
Abstract : We establish some coupled fixed point theorems for a mapping satisfying some contraction conditions in complete partial metric spaces. Our consequences extend the results of H. Aydi (2011).